Pembuatan Kroket Berbahan Dasar Talas (Colocasia Esculenta) Dan Penambahan Krimer Nabati Dengan Isian Ikan Tongkol Berbumbu Kare - Elvira Azmi Nafisah; Lilis Sulandari; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (Student Research Journal, 2023)
Croquettes are processed products from taro and the addition of vegetable creamer with a filling of tuna with curry spices. The aims of this study were 1) to determine the sensory quality of taro croquettes and the addition of vegetable creamer with cob curry seasoning 2) to determine the nutritional content based on laboratory tests including ash content, water content, protein, fat, and carbohydrates 3) to determine the cost of raw materials for taro croquettes . This type of research is an experiment. Techniques for collecting observational data by means of hedonic quality were carried out by 30 panelists. The independent variable of this research is the amount of creamer added. The dependent variable in this study was the organoleptic properties including shape, color, aroma, texture, taste and overall preference. The control variables in this study are the materials used, the equipment used and the manufacturing procedures. The data analysis technique in this study was a sensory test using a single ANOVA test and Duncan's advanced test. The results showed that 1) there was an effect on the sensory quality of making taro croquettes and the addition of vegetable creamer with curry cob fish filling 2) there was no effect on the production of taro croquettes and the addition of vegetable creamer 3) the selected products contained the same nutrition as or greater in the manufacture Taro croquettes filled with moringa leaves and oyster mushrooms.